2007
DOI: 10.1002/hep.21582
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of human embryonic stem cells into functional hepatic cells

Abstract: The differentiation capacity of human embryonic stem cells (hESCs) holds great promise for therapeutic applications. We report a novel three-stage method to efficiently direct the differentiation of human embryonic stem cells into hepatic cells in serum-free medium. Human ESCs were first differentiated into definitive endoderm cells by 3 days of Activin A treatment. Next, the presence of fibroblast growth factor-4 and bone morphogenetic protein-2 in the culture medium for 5 days induced efficient hepatic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
463
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 557 publications
(490 citation statements)
references
References 96 publications
18
463
1
3
Order By: Relevance
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, immunofluorescence staining was carried out to assess the coexpression of a panel of crucial transcription factors, including FOXA2, GATA4, HNF4A, GATA6, PROX1, HNF6 and TBX3, along with the mature hepatocyte markers ALB and CYP3A4 in hepatocyte-like cells differentiated from human embryonic stem cells (hESCs), according to a previously published protocol [5]. Although ALB was efficiently expressed and co-localized with HNF4A in hepatocyte-like cells differentiated from hESCs, CYP3A4 was rarely observed in the differentiated cultures (Supplementary information, Data S1 and Figure S1A-S1B).…”
mentioning
confidence: 99%
“…After the induction of hESCs through definitive endoderm cells [8] to ventral foregut cells ( Figure 1A and Supplementary information, Figures S2 and S3), the cells are recruited to the hepatic lineage. Because both BMP and FGF signals were included in our previous protocol [5], we postulated that an additional signal is required for hepatic PROX1 and HNF6 expression. Among the various conditions that we tested, we found that replating dissociated ventral foregut cells at a relatively low density (2 × 10 5 /ml) followed by treatment with induction factors (FGF7, BMP2 and BMP4) for 5 days greatly promoted the emergence of PROX1-and HNF6-expressing hepatoblast-like colonies; these colonies were also positive for AFP, HNF4A and TBX3 (Supplementary information, Figure S4).…”
mentioning
confidence: 99%
“…For instance, iPS cells had been engineered to differentiate into liver hepatocytes and pancreatic endocrine (Cai et al 2007;D'Amour et al 2006;Song et al 2009;Zhang et al 2009). Moreover, a recent study reported the successful directed differentiation of human iPS cells into functional intestinal tissue in vitro by manipulating a temporal series of growth factors (Spence et al 2011).…”
Section: The Evolving Concept Of the Cancer Stem Cell Modelmentioning
confidence: 99%